Manifesting the Crusaders’ Instinct for Violence in the Context of the Capture of Antioch - Çekiç, Ayşe (Journal of Al-Tamaddun, 2024)
This paper scrutinises the ideological foundations and violent practices of the Crusaders during the First Crusade, focusing specifically on the massacre at Antioch in 1098. It posits that the Crusaders’ notion of divine salvation was inherently linked to the brutalisation of non-Christian populations, particularly Muslims, whom they perceived as adversaries to Christian faith and sovereignty. By conducting a comparative analysis of Crusader and Muslim sources, this study investigates the development of a Crusader ethos that legitimised mass slaughter as a divinely sanctioned act. Antioch, a strategic waypoint en route to Jerusalem, held significant religious importance for Christians, thereby intensifying Crusader aggression. This massacre, driven by religious zeal and demographic ambitions, precipitated a transformative shift in the city’s populace and symbolised the Crusaders’ determination to re-establish Christianity in the East. Chronicles from the period, including those by Raymond d’Aguilers and Peter Tudebode, vividly describe the slaughter, often depicting it as fulfilling God’s will. The paper underscores how Crusader narratives celebrated this violence as divine retribution, setting a precedent for subsequent massacres in Maara and Bayt al-Maqdis. Ultimately, this study enhances our understanding of the Crusader mindset, particularly how it rationalised extreme violence against perceived ‘infidels’ as essential to fulfilling a holy mandate. The findings highlight the complexities of Crusader ideology, shaped by theological, cultural, and geopolitical factors, which influenced European perspectives on the Eastern world for centuries to come.